X-ray monitoring of classical novae in the central region of M 31 III. Autumn and winter 2009/10, 2010/11, and 2011/12 - Henze, M.; Pietsch, W.; Haberl, F.; Della Valle, M.; Sala, G.; Hatzidimitriou, D.; Hofmann, F.; Hernanz, M.; Hartmann, D. H.; Greiner, J. (2014)
Context. Classical novae (CNe) represent the major class of supersoft X-ray sources (SSSs) in the central region of our neighbouring galaxy M 31. Aims: We performed a dedicated monitoring of the M 31 central region, which aimed to detect SSS counterparts of CNe, with XMM-Newton and Chandra between Nov. and Mar. of the years 2009/10, 2010/11, and 2011/12. Methods: We systematically searched our data for X-ray counterparts of CNe and determined their X-ray light curves and also their spectral properties in the case of XMM-Newton data. Additionally, we determined luminosity upper limits for all previously known X-ray emitting novae, which are not detected anymore, and for all CNe in our field of view with recent optical outbursts. Results: In total, we detected 24 novae in X-rays. Seven of these sources were known from previous observations, including the M 31 nova with the longest SSS phase, M31N 1996-08b, which was found to fade below our X-ray detection limit 13.8 yr after outburst. Of the new discoveries, several novae exhibit significant variability in their short-term X-ray light curves with one object showing a suspected period of about 1.3 h. We studied the SSS state of the most recent outburst of a recurrent nova, which had previously shown the shortest time ever observed between two outbursts (~5 yr). The total number of M 31 novae with X-ray counterpart was increased to 79, and we subjected this extended catalogue to detailed statistical studies. Four previously indicated correlations between optical and X-ray parameters could be confirmed and improved. Furthermore, we found indications that the multi-dimensional parameter space of nova properties might be dominated by a single physical parameter, and we provide interpretations and suggest implications. We studied various outliers from the established correlations and discuss evidence of a different X-ray behaviour of novae in the M 31 bulge and disk. Conclusions: Exploration of the multi-wavelength parameter space of optical and X-ray measurements is shown to be a powerful tool for examining properties of extragalactic nova populations. While there are hints that the different stellar populations of M 31 (bulge vs. disk) produce dissimilar nova outbursts, there is also growing evidence that the overall behaviour of an average nova might be understood in surprisingly simple terms. Partly based on observations with XMM-Newton, an ESA Science Mission with instruments and contributions directly funded by ESA Member States and NASA.Tables 1-9 are only available at the CDS via anonymous ftp to http://cdsarc.u-strasbg.fr (ftp://130.79.128.5) or via http://cdsarc.u-strasbg.fr/viz-bin/qcat?J/A+A/563/A2
Keywords: Astrophysics - High Energy Astrophysical Phenomena; Astrophysics - Solar and Stellar Astrophysics; CATACLYSMIC VARIABLES; galaxies: individual: M 31; Novae; X-rays: binaries